2000
DOI: 10.1053/jhep.2000.8169
|View full text |Cite
|
Sign up to set email alerts
|

Low frequency of cirrhosis in a hepatitis C (genotype 1b) single-source outbreak in germany: A 20-year multicenter study

Abstract: batches of anti-D immune globulin contaminated with hepatitis C virus (HCV) genotype 1b (20,000-480,000 copies/dose) from a single erythrocyte donor had been administered for prophylaxis of rhesus isoimmunization throughout East Germany. All 2,867 women involved had been recalled after January 12, 1979 for repeated screening of alanine transaminase (ALT). They were prospectively followed in regional centers. We have reexamined a cohort of 1,018 women (median age 24, range 16-38 years at infection) on follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
223
1
17

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 329 publications
(254 citation statements)
references
References 40 publications
13
223
1
17
Order By: Relevance
“…These rates of viral clearance are consistent with other reports in nonhemophilic populations (1), although somewhat less than reported in children and young women infected through contaminated blood products (4,43). In the hemophilia cohort, repeatedly exposed to unsterilized blood products, it is possible that single episodes of spontaneous viral clearance were overshadowed by reinfection during subsequent exposures, as has been demonstrated in thalassemic patients who developed repeated episodes of acute hepatitis C following multiple exposures (44).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These rates of viral clearance are consistent with other reports in nonhemophilic populations (1), although somewhat less than reported in children and young women infected through contaminated blood products (4,43). In the hemophilia cohort, repeatedly exposed to unsterilized blood products, it is possible that single episodes of spontaneous viral clearance were overshadowed by reinfection during subsequent exposures, as has been demonstrated in thalassemic patients who developed repeated episodes of acute hepatitis C following multiple exposures (44).…”
Section: Discussionsupporting
confidence: 89%
“…Population-based studies in the United States indicate that approximately 75% of patients remain chronically infected with hepatitis C (1). In contrast, up to 50% of patients have been reported to spontaneously resolve hepatitis C infection when exposure occurred in children undergoing cardiac surgery or cancer chemotherapy, in young women after a common-source outbreak of contaminated anti-D immunoglobulin, or in healthcare workers after needlestick exposures (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas some studies showed that HCV carriers with normal ALT have mild and stable disease, others reported a significant progression of fibrosis in approximately 20%-30% of such patients. 3 In their first study 4 describing the 20-year follow-up of over 1,000 women infected in East Germany in January 1979 by contaminated anti-D immune globulin, the researchers reported that 26 patients should be considered as true healthy carriers (i.e., normal liver, normal ALT, and persistent HCV viremia). At 25-year follow-up, 5 only 11 women had remained in a healthy state, whereas the others had progressed to chronic hepatitis C (CHC).…”
Section: Liver Disease Progression In Hepatitis C Virus Carriers Withmentioning
confidence: 99%
“…1. Of the original 26 HCV carriers which we described at 20 years after infection, 4 HCV inhouse polymerase chain reaction (PCR) emerged as false-positive in three patients, unraveling a spontaneous resolution of HCV infection in these patients. Among the remaining HCV carriers, seven patients developed chronic hepatitis C as determined by elevated transaminases and clinical or histological signs of liver damage.…”
Section: Replymentioning
confidence: 99%